2016
DOI: 10.1016/j.jbiotec.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput process development of an alternative platform for the production of virus-like particles in Escherichia coli

Abstract: A c c e p t e d M a n u s c r i p t -Establishing a high-throughput procedure for miniaturized, parallel and automated cultivations, cell lysis and analytics of recombinant virus proteins -Optimizing the production of a promising virus-like particle-based nanocarrier for future chimeric vaccines in Escherichia coli -Yielding up to 1.63 mg of murine polyomavirus protein VP1 per mL cultivation medium with a total soluble protein portion of 43% by codon optimization and design of experiments -Developing a simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
(69 reference statements)
1
16
0
Order By: Relevance
“…Several studies have shown the results of induction profiles in 48-well Flowerplates but either at single temperatures [ 24 , 30 32 ] or with few data points [ 33 , 34 ]. The aim of this study was to comprehensively investigate the effect of temperature on optimal induction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the results of induction profiles in 48-well Flowerplates but either at single temperatures [ 24 , 30 32 ] or with few data points [ 33 , 34 ]. The aim of this study was to comprehensively investigate the effect of temperature on optimal induction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An eight‐well sonifyer for the release of virus‐like particles from E. coli was used by Ladd et al. . Another physical HT cell breakage system based on electric fields in parallel microfluidic channels was developed by Poudineh et al.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…A 24-well HT sonication device was used by Hohnadel et al [76] for 15 distinct cell types including gram-negative and -positive bacteria as well as fungi and yeasts. An eight-well sonifyer for the release of virus-like particles from E. coli was used by Ladd et al [77]. Another physical HT cell breakage system based on electric fields in parallel microfluidic channels was developed by Poudineh et al [78].…”
Section: Ht Cell Lysis Systemsmentioning
confidence: 99%
“…A popular noninvasive online‐monitoring device for microtiter plate cultivations is the BioLector device. Biomass and fluorescent products can simply be measured via scattered light (ScL) and fluorescence intensities, respectively . A decisive advantage is the noninvasive procedure, which allows measurement of samples without stopping the shaking process of the microtiter plate .…”
Section: Introductionmentioning
confidence: 99%
“…Biomass and fluorescent products can simply be measured via scattered light (ScL) and fluorescence intensities, respectively. [22][23][24][25][26][27][28][29] A decisive advantage is the noninvasive procedure, which allows measurement of samples without stopping the shaking process of the microtiter plate. 29 By using special microtiter plates equipped with optodes, also oxygen or pH can be detected.…”
Section: Introductionmentioning
confidence: 99%